Literacy Program Management in Improving Students’ Reading Interest: A Qualitative Case Study in Indonesian Elementary Schools - Ressy Risthiany; Maman Suherman (ITScience (Information Technology and Science), 2026)
This study examines how literacy program management contributes to improving students’ reading interest in elementary schools. Using a qualitative descriptive case study design, the research was conducted at SDN 1 Rawa and SDN 2 Lumbungsari in Ciamis Regency, Indonesia. Data were collected through in-depth interviews, field observations, and document analysis, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that the effectiveness of literacy initiatives is strongly influenced by principals’ managerial and leadership capacities rather than solely by the availability of facilities. Strategic planning, clear task organization, consistent daily reading routines, and continuous evaluation enabled the embedding of literacy practices into everyday school activities and learning processes. Despite challenges such as limited resources, low student motivation, and time constraints, schools adopted adaptive strategies, including collaboration with stakeholders, material rotation, and creative literacy activities, to sustain engagement. The study concludes that literacy development should be viewed as a systematic and school-wide management process. This research contributes to educational management literature by highlighting principal leadership as a key mediating factor linking literacy policy to sustainable reading culture in elementary education.